A Role Of Emotional Intelligence Improving Lecturer Performance - Harni, Budi (Lembaga Penelitian dan Pengabdian Nasyarakat Universitas Pakuan, 2018)
The objective of this study is to examine a role of emotional intelligence in improving lecturer performance. This study used a quantitative approach which surveyed 107 part-time of lecturers selected by a proportional random sampling of 3 (three) high school economics in Bogor. The result conveyed that there is positive and significant role of emotional intelligence in improving lecturer performance. It is shown that there is a positive significant between emotional intelligence with lecturer’s performance with coefficient correlation ry=0,632 and coefficient determination ry=0,400 (40%) with the regression equation Ŷ=27,86+0,8X1, Another factor that effects the variable lecturer’s of 60 %.